High-Resolution Ultrasound for Diagnostic Assessment of the Great Auricular Nerve – Normal and First Pathologic Findings - Lieba-Samal, D.; Pivec, C.; Platzgummer, H.; Gruber, G. M.; Seidel, S.; Bernathova, M.; Bodner, G.; Moritz, T. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: The great auricular nerve (GAN) is a sensory branch of the superficial cervical plexus. While its blockade is an established procedure, little is known about the ultrasound appearance of pathologic conditions of the GAN itself. We, therefore, aimed to evaluate the possibility of the visualization and diagnostic assessment of the GAN along its entire course by means of high-resolution ultrasound (HRUS).Materials and Methods: To assess the feasibility of visualization, we performed HRUS with an 18 MHz probe, HRUS-guided, fine-needle ink markings and consecutive dissection in six anatomical specimens. Then, we measured the diameter of the GAN in healthy volunteers and finally performed a retrospective review of patients referred for HRUS examinations because of pain within GAN territory between August 1, 2012 and August 1, 2013.Results: The GAN was clearly visible with HRUS from its formation to the final branches, and was marked successfully on both sides in all anatomical specimens (n = 12). The mean average in-vivo was 0.14 cm ± 0.03 (range 0.08 – 0.2). Seven cases of patients with GAN pathologies of various origins (idiopathic, traumatic, tumorous and iatrogenic) were identified, of which 6 were visible on HRUS and all of which could be confirmed by complete resolution of symptoms after selective HRUS-guided GAN block.Conclusion: This study confirms the reliable ability to visualize the GAN with HRUS throughout its course, both in anatomical specimens and in vivo. The provided cases show that pathologies of the GAN seem to have a variety of causes and may not be rare. We, therefore, encourage the use of HRUS in patients with unclear pain in the auricular, periauricular and posterior-lateral head.
Keywords: head/neck; ear; great auricular nerve; neuroma; neuropathic pain